Characterization of Non-Small Cell Lung Cancer Tissue by Quantitative Assessment of Class III β-Tubulin Expression - A. Lee; T. A. Bogush; A. N. Grishanina; I. P. Romanov; E. A. Bogush; S. A. Kaliuzhny; K. I. Chandran; A. M. Scherbakov; V. S. Kosorukov (Антибиотики и Химиотерапия, 2024)
Background. The cytoskeletal protein β-tubulin class III (Tubb3) is associated with tumor resistance to taxanes and vinca alkaloids, as well as with the metastatic potential of neoplasm, however, data from immunohistochemical analysis of Tubb3 expression in non-small cell lung cancer (NSCLC) tissue are few and contradictory. Purpose. Characterization of the level and intensity of Tubb3 expression in NSCLC tissue and analysis of the identified parameters correlation with clinically significant characteristics of the disease. Methods. Quantitative assessment of the level and intensity of Tubb3 expression in 120 surgical samples of NSCLC was carried out by immunofluorescence method associated with flow cytometry. Primary rabbit monoclonal antibodies specific to Tubb3 and secondary anti-rabbit antibodies conjugated with fluorescent dye DyLight650 (ab98510, UK) were used. The expression of the marker was assessed by two parameters: the level of expression measured as the percentage of the cells expressing Tubb3 and the intensity of expression in conventional units (CU) represented as the ratio of the geometric mean fluorescence intensity in the experimental and control samples (cells incubated with secondary antibodies only). Results. 1. Tubb3 expression was detected in all NSCLC samples studied. The median level and intensity of Tubb3 expression was 30.5% and 2.0 CU with significant differences (up to 10 times) in the quantitative values of both parameters in different patients. 2. The distribution of the studied tumors in terms of the level and intensity of Tubb3 expression differs from normal (P<0.001), the associative relationship between the assessed parameters is very strong (Spearman's rank correlation coefficient was 0.91; P<0.0001). 3. Statistical analysis did not reveal correlations between the level of Tubb3 expression and the gender and smoking status of the patients, with the degree of tumor differentiation, as well as with the stage of NSCLC. 4. In the group of lung adenocarcinomas, the median level of Tubb3 expression is higher compared with squamous cell lung cancer in male and female patients (P=0.01). Conclusion. High heterogeneity of Tubb3 expression level in NSCLC tissue in the patients and differences in the parameters between the tumors of various histotypes indicate the importance of further correlation analysis of Tubb3 expression level with the patients' life span in order to identify the prognostic value of the marker.